Pelayanan Vaksinasi Covid-19 Bagi Remaja Usia 12-17 Tahun Di Sentra Vaksinasi Poltekkes Kemenkes Palangka Raya - Seri Wahyuni; Greiny Arisani; Noordiati Noordiati; Wahidah Sukriani; Wijaya Atmaja Kusuma; Titik Istiningsih (Universitas Muhammadiyah Mataram, 2022)
Abstract: : Vaccination activities for adolescents aged 12-17 years at the Vaccination Center of the Health Poltekkes Palangka Raya are a form of community service. The purpose of the COVID-19 vaccination service is to protect adolescents from exposure to COVID-19, establish herd immunity, and provide security when they carry out face-to-face learning (PTM). The method of implementing this activity includes socialization, taking care of activity permits, preparing suggestions and infrastructure, preparing officers, implementing, evaluating. The number of participants who were vaccinated was 6000 teenagers from various junior and senior high schools in Palangka Raya City, with a duration of 13 days. Recipients of adolescent vaccines who meet the requirements as many as 6000 people with dose 1 vaccination, 3 people with mild Post-Immunization Adverse Events (AEFI).Abstrak: Kegiatan Vaksinan bagi remaja usia 12-17 tahun di Sentra Vaksinasi Poltekkes Kemenkes Palangka Raya merupakan bentuk pengabdian kepada masyarakat. Tujuan pelayanan vaksinasi COVID-19 adalah melindungi para remaja dari paparan COVID-19,membentuk herd immunity, dan memberikan keamanan saat mereka melaksanakan pembelajaran tatap muka (PTM). Metode pelaksanaan kegiatan ini meliputi sosialisasi, mengurus perijinan kegiatan, menyiapkan saran dan prasarana, penyiapan petugas, pelaksanaan, evaluasi. Jumlah peserta yang divaksin sebanyak 6000 remaja dari berbagai SMP dan SMA di Kota Palangka Raya, dengan lama pelaksanaan selama 13 hari. Penerima vaksin remaja yang memenuhi syarat sebanyak apaian vaksinasi dosis 1 sebanyak 6000 orang, Kejadian Ikutan Pasca Imunisasi (KIPI) ringan sebanyak orang 3 orang.